2009
DOI: 10.1186/1471-2458-9-148
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity inversely associated with the presence of depression among urban adolescents in regional China

Abstract: Background: An inverse relationship between physical activity (PA) and depression among adolescents has been reported in developed communities without consideration of sedentary behaviors (SB, including sitting for course study, viewing TV, and sleeping). We explored the association between recreational PA time (hr/wk) and depression after adjustment with SB and other possible confounders among Chinese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 35 publications
(17 reference statements)
10
61
3
5
Order By: Relevance
“…The negative association between depressive symptoms in students and the frequency of extracurricular physical activity in school and other physical activity outside the school found in this study was consistent with the findings of previous cross-sectional and prospective studies in adolescents [22,24,25,28]. This inverse relationship might be explained in terms of both biological and psychosocial mechanisms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The negative association between depressive symptoms in students and the frequency of extracurricular physical activity in school and other physical activity outside the school found in this study was consistent with the findings of previous cross-sectional and prospective studies in adolescents [22,24,25,28]. This inverse relationship might be explained in terms of both biological and psychosocial mechanisms.…”
Section: Discussionsupporting
confidence: 82%
“…On the contrary, higher SES in childhood was reported to affect the onset of depression [16]. Other factors such as exposure to acute stressful events and chronic adversity, e.g., history of abuse and bullying [17], poor body image [18][19][20][21], ''almost never''-categorized extracurricular physical activity in school and other physical activity outside the school [22][23][24][25][26][27][28], and sleep duration [29,30], were reported to affect depressive symptoms in adolescents. Moreover, an association between depressive symptoms and low levels of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and dietary B vitamins, particularly folate and vitamin B-6 has been suggested in Japanese adolescents [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…En trabajadores japoneses se ha descrito una menor frecuencia de SD en quienes tienen AF regular, así como mejoras en la SD en participantes de un programa de AF (13) . Asimismo, estudios en adolescentes, adultos, mujeres en edad mediana y adultos mayores tienen resultados similares (6)(7)(8)(9) y se ha observado un efecto terapéutico de la AF en pacientes deprimidos (14) , el cual podría ser dosis dependiente (15) . Aunque, otros autores biológicas: la termogénesis, la basada en endorfinas y la de las monoaminas; y psicológicas: la de la distracción y la del aumento de la autoeficacia.…”
Section: Discussionunclassified
“…Ante mayores niveles de AF, existe una menor probabilidad de desarrollar sintomatología depresiva (SD) (6) en adolescentes y una disminución de SD en adultos jóvenes (7) . Una mayor AF se asocia a menor frecuencia de trastorno depresivo en mujeres en edad mediana (8) y en ancianos (9) .…”
Section: Introductionunclassified
“…Research has often confirmed the positive association between physical activity and health indicated (Abu-Omar et al 2008, Barros et al 2009, Hamer et al 2009, Hong et al 2009, Janssen and Leblanc 2010, Page and Suwanteerangkul 2009). However, a clear distinction has been noted between town and countryside in the strength of the link between physical activity and the health of young people.…”
Section: Discussionmentioning
confidence: 99%